Implications of the non‐neuronal cholinergic system for therapeutic interventions of inflammatory skin diseases - Qu, Hui‐Qi; Kao, Charlly; Hakonarson, Hakon (Experimental dermatology, 2024)
The pivotal roles of acetylcholine (ACh) in physiological processes encompass both the nervous and non‐neuronal cholinergic systems (NNCS). This review delineates the synthesis, release, receptor interactions, and degradation of ACh within the nervous system, and explores the NNCS in depth within skin cells including keratinocytes, endothelial cells, fibroblasts, macrophages, and other immune cells. We highlight the NNCS's essential functions in maintaining epidermal barrier integrity, promoting wound healing, regulating microcirculation, and modulating inflammatory responses. The potential of the NNCS as a therapeutic target for localized ACh regulation in the skin is discussed, though the translation of these findings into clinical practice remains uncertain due to the complexity of cholinergic signalling and the lack of comprehensive human studies. The review progresses to therapeutic modulation strategies of the NNCS, including AChE inhibitors, nicotinic and muscarinic receptor agonists and antagonists, choline uptake enhancers, and botulinum toxin, highlighting their relevance in dermatology. We highlight the impact of the NNCS on prevalent skin diseases such as psoriasis, atopic dermatitis, rosacea, acne, bullous diseases, hyperhidrosis and hypohidrosis, illustrating its significance in disease pathogenesis and therapy. This comprehensive overview aims to enhance understanding of the NNCS's role in skin health and disease, offering a foundation for future research and therapeutic innovation.